Peran Pemerintah Desa Dalam Kelompok Tani Sombor Wanua Talumengan Di Kelurahan Kakaskasen Tiga Kecamatan Tomohon Utara Kota Tomohon - Sebayang, Imel Melinia Br; Maweikere, Audrey Julia Maria; Tambas, Jane Sulinda (AGRI-SOSIOEKONOMI, 2024)
The aim of the research is to determine the role of the village government in the Sombor Wanua Talumengan Farmer Group in Kakaskasen Tiga Subdistrict, North Tomohon District, Tomohon City. This research lasted for 4 months from May to August 2023. The data used in this research was primary data obtained based on interviews with nine informants from the Sombor Wanua Talumengan farmer group, including administrators and members, taken using purposive sampling (randomly) and secondary data obtained from agencies related to the research carried out. Data analysis used is descriptive. The results of this research show that the role of the Village Government in the Sombor Wanua Talumengan Farmer Group in Kakaskasen Tiga Subdistrict, North Tomohon District, Tomohon City has not been fully implemented optimally, this is seen from the aspect of the government as a regulator of rules/mechanisms, and government policies have not been achieved and are not in accordance with the hopes of farmer groups, because they were not able to prepare well. The government as a dynamist, namely (1) Socialization, (2) Mentoring, (3) Training, and (4) Field visits are still lacking because farmer groups have not received socialization and assistance but for training and field visits farmer groups have received it and the government as Facilitators as providers of superior seeds, fertilizer and production facilities have been able to facilitate farmer groups well.